Sarcomatoid Variant of Urothelial Carcinoma of the Renal Pelvis with Inferior Vena Cava Tumour Thrombus: A Case Report and Literature Review - Sameera Rashid; Mohammed Akhtar (Case Reports in Pathology)
Sarcomatoid variant of urothelial carcinoma (SVUC) of the renal pelvis is a rare entity. To the best of our knowledge, around 25 cases of this neoplasm have been reported in the literature to date, most of which were of high stage. The inferior vena cava tumour thrombus, which is a hallmark of renal cell carcinoma (RCC), may rarely be found in urothelial carcinoma of renal pelvis. In this report, a case of SVUC associated with tumour extension to inferior vena cava is documented. This association has been encountered in only one previously reported case. The possibility of urothelial carcinoma of the renal pelvis should therefore be included in the differential diagnosis of tumour thrombus of the inferior vena cava.